The Role of Digital Marketing Resilience in Mediating the Relationship Between Entrepreneurial Marketing and Business Performance in Service SMEs - Syafi'ah; Melan Susanty Purnamasari; Juli Handayani; Delaga Nurwisda; Rustina Dewi Werdiasih; Dewi Puspasari (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2025)
This study aims to examine the role of Entrepreneurial Marketing in enhancing Business Performance through the mediation of Digital Marketing Resilience in small and medium-sized enterprises (SMEs) in the service sector in Indonesia. The research adopts a quantitative approach with a sample of 100 SMEs, selected using Slovin’s formula with a 10% margin of error. Data were collected through a survey using Google Forms, and the analysis was conducted using SmartPLS. The study investigates the relationships between the three key variables: Entrepreneurial Marketing, Digital Marketing Resilience, and Business Performance. The results show that Digital Marketing Resilience has a significant positive effect on Business Performance. However, Entrepreneurial Marketing does not have a direct effect on Business Performance, but it significantly influences business performance when mediated by Digital Marketing Resilience. This indicates that entrepreneurial marketing strategies, such as innovation, proactivity, and risk-taking, enhance business performance indirectly through building digital resilience. The findings highlight the importance of integrating entrepreneurial marketing with resilient digital marketing strategies to drive better business performance. This research provides valuable insights for SMEs aiming to optimize their marketing strategies and adapt to the challenges of the digital era.